Freezing point and thermal conductivity of tropical fruit pulps: Mango and papaya - Telis, V. R N [UNESP]; Telis-Romero, J. [UNESP]; Sobral, P. J A; Gabas, A. L. (Taylor & Francis, 2007)
The freezing point depression of mango and papaya pulps was measured by using a simple apparatus, consisting of two major sections: a freezing vessel and a data acquisition system. The thermal conductivity of both pulps as a function of frozen water fraction and temperature was also investigated by using a coaxial dual-cylinder apparatus. Thermal conductivity above the initial freezing point was well fitted by polynomial equations. Below the freezing point, the thermal conductivity was strongly affected by both the frozen water fraction and temperature. Simple equations in terms of frozen water fraction and temperature could be fitted to the experimental data of freezing point depression and thermal conductivity.
Keywords: Freezing point depression; Fruit pulps; Thermal conductivity; Freezing; Fruits; Frozen water fraction; Papaya; Pulp; Mangifera; Melting Point; Pulps; Thermal Conductivity; Carica papaya